Family Support for Diabetes Self-care Behavior in T2DM Patients who Use Herbs as a Complementary Treatment (Medico Legal Update, 2019)
This study aims to identify family support for the use of herbs as complementary treatments based on diabetes self-management in regulating blood sugar levels in patients with Type 2 Diabetes Mellitus (T2DM) in Surabaya City East Java Indonesia, using cross-sectional approach. Participants were collected from 7 public health center in Surabaya using simple random sampling with a sample size of 230. Data were collected with a questionnaire, then analyzed using PLS. The indicator of characteristic of disease and family support had factor loading >0.6. There was influence of disease characteristics and family support on the use of herbs. The use of herbs had an effect on blood sugar regulation. Family support was necessary for patients to keep diabetes self-management when T2DM patients use herbs.